(untitled) (Al-Farooq Journal of Sciences, 2026)
This research paper examines the extent to which the traditional rules of liability for things, as stipulated in Article (181) of the Libyan Civil Code, can accommodate damages caused by artificial intelligence systems. Given the legislative void in Libyan law regarding AI regulation, the study adopts a comparative analytical approach to assess the legal feasibility of applying the concepts of "thing" and "custody" to autonomous algorithms and smart robots. The research addresses key interpretive challenges, including the criterion of direct supervision and the determination of the actual custodian. The findings suggest that the current provisions are insufficient to cover AI-related harms, calling for either a broad interpretation of the existing text or the enactment of a specialized legislative framework.